INOVASI BIOPOT BERBAHAN JERAMI PADI SEBAGAI SUBSTITUSI POLYBAG PEMBIBITAN DI DESA SIDOREJO, BOJONEGORO - Siti Nikmatin; Irmansyah Irmansyah; Abd Djamil Husin; Rima Fitria Adiati; Naufal Luthfi Ahya (Jurnal AbdiMas Nusa Mandiri, 2026)
The abundance of rice straw biomass waste in Desa Sidorejo, Kabupaten Bojonegoro, has not been managed optimally and can cause environmental problems. On the other hand, the use of plastic polybags in seedling cultivation contributes to the accumulation of non-biodegradable plastic waste. The objective of this community service project is to introduce an innovation in the production of biopots from nonwoven geotextile sheets made from rice straw fibers. The straw is bonded using simple roll-press technology to create geotextile, and the final product can be used as a substitute for plastic polybags. The activity partners were the “Karya Tani” farmer group, consisting of 20 participants. The implementation methods included outreach, training, and evaluation. Evaluation was conducted through pre-tests and post-tests, as well as field observations over a three-month period. Evaluation results showed a significant increase (100%) in knowledge and skills. Meanwhile, regarding attitude, 76% of participants engaged in bio-pot production to utilize their free time. The implications of this activity include a reduction in agricultural waste and dependence on plastic in Sidorejo Village, while also opening opportunities for the development of creative business units based on a circular economy for the local farmers’ group.